Properties of 1-butyl-3-methylimidazolium chloride (BMIMCL) Treated Sawdust-Reinforced Polyethylene Composite - Othman, Abdullah (2020)
In this research, composites based on untreated, treated sawdust and pre-treatment on treated sawdust with Polyethylene (PE) were prepared using injection moulding machine. Raw sawdust was chemically treated with 1-butyl-3-metylimidazeluim Chloride (BMIMCL) and Cetyl Trimethyl Ammonium Bromide (CTAB) to improve the properties of composites. The amorphous and crystallinity were studied using X-Ray Diffraction(XRD). Results from flexural testing and tensile testing that indicate mechanical properties enhanced when pre-treated occurred on sawdust reinforced PE composites compared to without pre-treatment. The surface morphologies obtain from Field Emission Scanning Electron Microscope (FESEM) possess surface roughness and weak interfacial adhesion, while the pre-treatment sawdust with CTAB showed improved in filler-matrix interaction. This indicate that better dispersion of the sawdust with PE matrix occurred upon chemical treatment of sawdust.